Monkeypox virus: A review. (March 2023) - Letafati, Arash; Sakhavarz, Tannaz
Abstract: While monkeypox was previously found in Africa, the bulk of occurrences in the present outbreak are being reported in many countries. It is not yet known how this outbreak began, and as the COVID-19 crisis begins to abate, numerous nations throughout the world are now contending with a novel outbreak. Monkeypox is a transmissible virus between animals and humans, belonging to the Orthopoxvirus genus of the Poxviridae family. In the 1970s, cases of monkeypox began increasing due to the cessation of vaccination against smallpox, which drew international attention. The virus was named monkeypox because it was first observed in macaque monkeys. It is thought to be transmitted by several different rodents and small mammals, though the origin of the virus is not known. Monkeypox, while occasionally transmitted from one human to another, can be disseminated through the inhalation of droplets or through contact with the skin lesions of an infected individual. Unfortunately, there is no definitive cure for monkeypox; however, supportive care can be offered to ameliorate its symptoms. In severe cases, medications like tecovirimat may be administered. However, there are no established guidelines for symptom management in monkeypox cases. In this article we have discussed about different aspects of monkeypox including viral structure, transmission, replication, clinical manifestations, vaccination, treatment and current prevalence in the world to understand it better and give insight to the future studies. Highlights: as the COVID-19 crisis begins to abate, countries throughout the world are now contending with a novel outbreak of monkeypox. Monkeypox transmission is mainly through droplets and is highly contagious following second viremia within the body. rashes develop around 1–3 days after the onset of fever and swollen lymph nodes. Tecovirimat, cidofovir, and immunoglobulin vaccinia (IVG), could potentially be used to treat monkeypox.